Zingiber officinale ameliorates allergic asthma via suppression of Th2-mediated immune response. (March 2015) - Khan, Asad Mahmood; Shahzad, Muhammad; Raza Asim, M. B.; Imran, Muhammad; Shabbir, Arham
Abstract Context: Ginger has been used commonly in the traditional system of medicine for the treatment of respiratory disorders. Objective: The present study investigates the immunosuppressive activity of ginger by using the mouse model of ovalbumin-induced allergic asthma. Materials and methods: Treatment with ethanol extract (500 mg/kg) and aqueous extract (720 mg/kg) of rhizomes, and methylprednisolone (5 mg/kg) was initiated 1 week after second sensitization of mice with ovalbumin and continued for 7 d. RT-PCR followed by gel electrophoresis and ELISA were used for the evaluation of mRNA expression levels and protein levels of Th2 type markers, respectively. Lung tissue histopathology was conducted by using H&E and PAS staining. Results: We observed significant reduction in goblet cell hyperplasia (0.83 ± 0.17 and 1.0 ± 0.26), infiltration of inflammatory cells in airways (0.67 ± 0.33 and 1.0 ± 0.37), and edema with vascular congestion (1.0 ± 0.26 and 1.2 ± 0.17) by both ethanol and aqueous extracts, respectively. A highly significant reduction of total and differential count of eosinophils and neutrophils in BALF, and eosinophil count in blood were also observed. Both extracts significantly inhibited Th2-mediated immune response, which is evident by a decrease in mRNA expression levels of IL-4 and IL-5. Protein levels of IL-4 and IL-5 in BALF, along with total serum IgE levels, were also significantly suppressed by both extracts. Discussion and conclusion: Our study validated the traditional use of ginger in respiratory disorders and suggests that ginger reduces allergic airway inflammation, possibly by the suppression of Th2-mediated immune response.